Iron-organic carbon coprecipitates reduce nitrification by restricting molybdenum in agricultural soils - Slimani, Imane; Doane, Timothy; Zhu-Barker, Xia; Lazicki, Patricia; Lybrand, Rebecca A.; Zaharescu, Dragos G.; Horwath, William (Frontiers in Materials, 2024)
Nitrification converts ammonium (NH4 + ) to nitrate (NO3 -) using metalloenzymes, the activity of which depends on iron (Fe), molybdenum (Mo), and copper (Cu) availability. Iron-organic carbon coprecipitates (or Fe-OC flocs) are key byproducts of wastewater treatment industry and natural components of soil that may affect nitrification by changing the bioavailability of these metals. Here, we used flocs of different chemistry (aromatic and aliphatic) and known Fe and C composition to investigate their effects on nitrification in soils along a soil C gradient. Both aromatic and aliphatic flocs reduced net nitrification, but the magnitude of their effect was more pronounced in soils with low C content as opposed to those with high C content. Within each soil, both flocs reduced net nitrification similarly. In the presence of flocs, the bioavailability of Mo (assessed by changes in the concentration of water-soluble Mo) was dramatically decreased in low C soils, possibly because Mo was incorporated into or adsorbed to flocs or their decomposition products. In contrast, Mo bioavailability in high C soils was decreased to a lesser extent by flocs, likely because organic matter (OM) limited floc adsorption capacity and released Mo through mineralization. The depletion of bioavailable Mo by flocs in agricultural soils has the potential to impede soil nitrification and extend the residence time of NH4 + and its availability to plants and microbes.